(untitled) (DAPesquisa, 2024)
The present work investigates the artworks of the Franco-Venezuelan Carlos Cruz-Diez (1923-2019) to understand, through Research in Arts (REY, 2002), his articulations between materialities and technologies in the constitutive process of their operative concepts for the installation of color-spaces as chromatic operations within the phenomenological context of perception (MERLEAU-PONTY, 2018). In this sense, Cruz-Diez’s proposal causes the dynamic viewer (BORTULUCCE, 2013) to explore the experience of the chromatic phenomenon in its event supports, making the viewer develop an occupation of space-time through the concept of "enation" (VARELA et al., 2000), enjoying parts while building their knowledge about the whole of the work.